Creating Student Loyalty Through the Value of Context-Based Customer Education - Muji Gunarto; Purwanto Purwanto; Dita Amanah; Dedy Ansari Harahap (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objective: The objective of this research is to find out how the Covid-19 pandemic forces the learning process at all levels of education including higher education to be carried out online, where face-to-face meetings are not allowed. How the influence of relational contact and physical context on context-based customer education and on the value of student experience and student loyalty in private universities is the aim of this study.Methodology: The survey was conducted in three major cities in Indonesia, namely Palembang, Bandung, and Surabaya with a total sample of 280 students. Characteristics of respondents based on age, gender, and semester of the three samples of cities are relatively homogeneous. Data analysis was carried out using a structural equation model (SEM) approach with the help of LISREL software.Finding: The results showed that the relational context had a positive and significant effect on context-based customer education, but the physical context had no effect. Context-based customer education has a positive effect on the value of student experience and student loyalty.Conclusion: Even though learning is done through online, students hope that there will be a strong interaction between lecturers and students, so that in lectures, at least it is carried out using blended learning. Strong interaction between students and lecturers is a context-based customer (student) education that can improve the student experience and have an impact on student loyalty to their alma mater.